The Boasians : founding fathers and mothers of American anthropology - Adams, William Y. (William Yewdale), 1927-2019 (Hamilton Books, an imprint of Rowman and Littlefield, 2016)
This book is a study in depth of the work of Franz Boas and twenty of his students at Columbia University in the early years of the twentieth century. Collectively they laid the entire institutional as well as the intellectual foundations of American anthropology as it exists today.